Correlation Analysis Between Ovarian Reserve and Thyroid Hormone Levels in Infertile Women of Reproductive Age - Wu, Jie; Zhao, Ying-jie; Wang, Min; Tang, Ming-qiang; Liu, Yao-fang (Frontiers in Endocrinology, 2021)
Objective: To analyze the correlation between ovarian reserve and thyroid function in women with infertility. Methods: Retrospective analysis of the data of 496 infertility patients who visited the clinic between January 2019 and December 2020. According to the TSH level, it is grouped into <2.5 mIU/L, 2.5 4.0mIU/L and ≥4.0 mIU/L or according to the positive/negative thyroid autoimmune antibody. The relationship was assessed through the ovarian reserve, thyroid function, and anti-Müllerian hormone (AMH) levels in infertile patients. On the other hand, the patients are divided into groups according to age (≤29 years old, 30-34 years old and ≥35 years old), basic FSH (<10 IU/L and ≥10 IU/L), and AMH levels. The ovarian reserve was evaluated through the AMH and the antral follicle count (AFC). Results: The average age of the patients was 30.31±4.50 years old, and the average AMH level was 5.13±4.30 ng/mL. 3.63% (18/496) of patients had abnormal TSH levels (normal: 0.35-5.5 mIU/L), the positive rate of thyroid peroxidase antibody (TPOAb) was 14.52% (72/496), the positive rate of anti-thyroglobulin antibody (TgAb) was 16.94% (84/496), and the positive rate of TPOAb and TgAb was 10.48% (52/496). After grouping according to TSH level or thyroid autoimmune antibody positive/negative grouping, the analysis found that there was no statistical significance in age, AMH level and basic FSH level among the groups (P>0.05). There were no significant differences in the levels of TSH, FT3, and FT4 among different ages, AMH, and FSH levels (P>0.05). Conclusion: There is no significant correlation between ovarian reserve and thyroid function in infertile women.